The survival, development, and reproduction of Gonipterus platensis (Coleoptera: Curculionidae) on the main Eucalyptus (Myrtaceae) genotypes planted in Brazil - de Oliveira, Nádia Cristina [UNESP]; Ribeiro, Murilo Fonseca [UNESP]; Ottati, Angelo; de Souza Tavares, Wagner; Serrão, José Eduardo; Zanuncio, José Cola; Zanetti, Ronald; Wilcken, Carlos Frederico [UNESP] (PeerJ, 2022)
Background. Gonipterus platensis Marelli (Coleoptera: Curculionidae) is the main defoliating beetle of Eucalyptus L'Hér. (Myrtaceae) plants worldwide. The suitability of Eucalyptus to this pest varies among host plant genotypes. The objective of this study was to evaluate the development, reproduction, and survival of G. platensis on Eucalyptus species and hybrids to assess their suitability to this insect pest in Brazil. Methods. The survival, development, and reproduction parameters were evaluated with G. platensis feeding leaves of Eucalyptus camaldulensis Dehnh., Eucalyptus grandis W. Hill., Eucalyptus urophylla S.T. Blake and on the hybrids of E. grandis ×E. urophylla 'H13' and 'VR3748' in the laboratory. Results. The duration of the larval stage of G. platensis was shorter on E. urophylla. The pupal stage and the period from larva to adult were equally shorter on E. urophylla and E. camaldulensis. The viability of instars of this insect was low on both E. grandis and E. camaldulensis. The complete lifespan, oviposition period and reproduction parameters of G. platensis were greater on E. urophylla, lower on E. camaldulensis and E. grandis, and intermediate on both hybrids tested. Synthesis. Eucalyptus urophylla is the most suitable host for G. platensis survival, development, and reproduction, while E. grandis and E. camaldulensis are the least suitable.
Keywords: Bioecology; Eucalypt hybrid; Eucalyptus camaldulensis; Eucalyptus grandis; Eucalyptus snout beetle; Eucalyptus urophylla